Pengaruh Fraksi Volume dan Ukuran Partikel Cangkang Telur Ayam terhadap Kekuatan Impak Komposit Polyester - Iskandar, Ihsan; Wahyudi, Haris (ROTASI, 2024)
The eggshell of chicken, as a waste product from the food industry, has garnered attention in environmental sustainability efforts. In the context of composites, chicken eggshell offers the potential as an economical and sustainable reinforcement. The use of reinforcing materials in the form of particles is a common approach in composite development. Despite research on the use of chicken eggshell as a reinforcement in composites, the comprehensive effects of content and various particle sizes on unsaturated polyester composites using chicken eggshell on impact strength have not been thoroughly explained. This research aims to fill this knowledge gap by investigating the influence of content and particle size of chicken eggshell on the impact strength of unsaturated polyester composites. Composites were prepared using Polyester UPR 108 matrix reinforced with chicken eggshell that had been crushed into powder with various particle sizes of 40 mesh, 60 mesh, 80 mesh, and 100 mesh. The variation in the volume fraction of particles used was 0%, 10%, 30%, and 50%. The influence of particle size on composite performance was evaluated using Charpy impact strength testing according to ISO 179-1 standards. The research results showed that pure resin had the lowest impact strength, at 1.09 kJ/m2. Test specimens with 100 mesh particle content had the highest impact strength, at 4.25 kJ/m2. These findings indicate that composites with smaller particle sizes tend to have higher impact strength